COLOR PATTERN OF TARO CATTLE - Noviolita, Yolla; Susari, Ni Nyoman Werdi; Widyastuti, Sri Kayati; Suatha, I Ketut; Heryani, Luh Gde Sri Surya (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023DO - 10.24843/bulvet.2023.v15.i05.p03, 2023)
Taro cattle are a group of cattle that are uniquely different from Balinese cattle with a relatively small population and reared in Taro Village, Tegallalang District, Gianyar Regency, Bali and are sanctified and used in religious ceremonies. Taro cattle are characterized by white hair, skin, iris, hooves, and horns. The difference in hair/skin color of taro cattle is due to the influence of melanin pigment. This study is an observational study using purposive sampling technique where 52 male and female taro cattle skin observations were made at Yayasan Lembu Putih with the aim of providing information and scientific evidence as well as guidelines and references for further research. The data obtained were then analyzed using relative frequency (percentage). The results showed that there are other colors found. There are six colors of taro cattle, putih kemerahan color with a total of 40.39%, in females as much as 32.69% and males 7.69%; putih gading color with a total of 38.46%, in females 17.31% and males 21.15%; putih color with a total of 1.92% which is only found in females; sudamala and cemeng colors are only found in the male population 7.69% and 3.85% respectively; and coklat color is only found in the female population as much as 7.69%. Improvements are needed in breeding and mating management, recording systems and checking taro cattle regularly every year.